A violência no discurso do adolescente : uma abordagem cognitiva - Araujo, Daniela (2014)
The guiding interest of this thesis was to understand how the concept VIOLENCE emerges fromthe discourse of adolescents of different social groups in the urban areaof Porto Alegre. The overall objective was to investigate, within of field of Cognitive Linguistics (CL), specifically Cognitive Semantics (SC), which processes and structures are involved in categorizing VIOLENCE-verifying the application of the Idealized Cognitive Model Theory. This study was based onthe analysis of questionnaires and texts produced by adolescents fromthe urban area of Porto Alegre, which were separated into two groups, according to the specific purposes of this study : 1) adolescents with no backgroundof violent experiences,who are prime area residents who study in private schools, in the central area of the city which have a highcost and no record of problems related to violence, and 2) adolescents victimized (victims, who experencie,observers, participantsin situations involving social, urban and family violence), who study in a public school located in a region dominated by the drug trafficwar. The study was approved by the Ethics Committee, under the registration number 16732913.7.0000.5336, and authorized by the legal guardians of the participating adolescents. The main objective was divided into specific objectives: A) identify and analyze the structure of the category VIOLENCEin terms ofconceptual networks, building metaphorical and metonymicmappings of the adolescents, B) compare if there are differences betweenthe form of the category structure and its VIOLENCE conceptual grading between groups of adolescents, to examine ifthere is a relationship between the social and cultural environmentand the elaborated concepts. The hypotheses that guided this research were: A) cognitive structure and gradation of the concept VIOLENCE differ among selected groups; B) social and cultural aspects influence the categorization of VIOLENCE; and C)The Cognitive Model Theory in a contextual situation, like this one, is justified because its relation with culture and cognition, which proves, one more time, its applicative character in socio-cultural experiences. . It was verified,based on the analysis of the corpus, that there was a distance between the adolescents of the first group and their related types of violence. These adolescents, when structuring VIOLENCE in linguistic expressions used FORCE as its basic element, relating it to the experiences of global scope, such as wars, robberies, fights.However, the second group when structuring VIOLENCE in linguistic expressionsdemonstrated more emotional involvement, resulting from their bodily experiences. It was noticed, that in their reports,FORCE was the basic element, but their focus of analysis was more related to PHYSICAL DAMAGE, and PSCOLOGICAL-EMOTIONAL-MORAL DAMAGE, because scenarios described as the typical examples of violence were scenarios in which such students had lived. The DOMESTIC VIOLENCE frame was predominant in their texts, what shows us that the concept isnotthought in a global way, as a phenomenon, but interpersonally. It was proved that the way adolescents conceptualize VIOLENCE is different, because the bodily experiences influence the way we structure a concept. So, we conclude that the linguistic expressions of a concept permeate the living experiences, therefore,the IdealizedCognitiveModelTheoryisuseful forstudies of experimentalnature,involvingcognition, society andculture.